(untitled) (World Economics and Finance Bulletin, 2024)
The following article describes the significance of thoroughly evaluating and managing risks associated with investment projects in order to enhance the overall business and investment climate within the national economy. It underscores the importance of utilizing various methods for qualitative risk assessment, such as SWOT analysis, 4P Marketing mix, and Delphi methods, to properly gauge the potential risks and benefits of undertaking a particular project. By implementing these strategies, businesses can make more informed decisions regarding their investments and ultimately improve their chances of success in the market.